2017
DOI: 10.1128/iai.00354-17
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Has Both Cytochrome bd -Type and Cytochrome aa 3 -Type Terminal Oxidases, Which Allow Growth at Different Oxygen Levels, and Both Are Important in Infection

Abstract: Listeria monocytogenes is a foodborne pathogen responsible for a number of life-threatening infections of humans. During an infection, it invades epithelial cells before spreading from the intestine to the cells of the liver and spleen. This requires an ability to adapt to varying oxygen levels. Here, we demonstrate that L. monocytogenes has two terminal oxidases, a cytochrome bd-type (CydAB) and a cytochrome aa3-type menaquinol (QoxAB) oxidase, and that both are used for respiration under different oxygen ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…The last gene in the salt shock induced operon, pdhD, was upregulated at all times, however, this was not significant (p > 0.05) after desiccation for 6 and 24 h in Lm 568 and Lm 08-5578, respectively. The σ B -regulated quinol oxidase operon (qoxABCD), which encodes cytochrome aa 3 and is involved in oxidative stress response and required for aerobic growth (Corbett et al, 2017;Liu et al, 2017a), was part of the shared core response to desiccation with upregulation of all four genes ( Table 2). The importance of oxidative stress is supported by the observed upregulation of ctaB, which is needed for biosynthesis of the prosthetic group in cytochrome aa 3 (Svensson et al, 1993).…”
Section: Strain Independent Core Desiccation Stress Response In L Momentioning
confidence: 99%
“…The last gene in the salt shock induced operon, pdhD, was upregulated at all times, however, this was not significant (p > 0.05) after desiccation for 6 and 24 h in Lm 568 and Lm 08-5578, respectively. The σ B -regulated quinol oxidase operon (qoxABCD), which encodes cytochrome aa 3 and is involved in oxidative stress response and required for aerobic growth (Corbett et al, 2017;Liu et al, 2017a), was part of the shared core response to desiccation with upregulation of all four genes ( Table 2). The importance of oxidative stress is supported by the observed upregulation of ctaB, which is needed for biosynthesis of the prosthetic group in cytochrome aa 3 (Svensson et al, 1993).…”
Section: Strain Independent Core Desiccation Stress Response In L Momentioning
confidence: 99%
“…The flexibility of bacterial respiratory chains facilitates adaptation to changing environments, and in many situations the bd oxidase becomes critical under conditions where the bc 1 /aa 3 complex is inhibited. In pathogens such as E.coli, Listeria monocytogenes, and Salmonella typhimuirium, the requirement for the cytochrome bd oxidase in bacterial virulence has been attributed to its role in resisting hypoxia and nitrosative and oxidative stress (23)(24)(25)(26). While previous studies in M. marinum and M. smegmatis found that the mycobacterial bd oxidase can also confer resistance to hypoxia and peroxide, the specific roles played by the cytochrome bd and bc 1 /aa 3 oxidases of Mtb during infection has been less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to pathophysiology, cytochrome oxidases are expressed in a number of bacterial pathogens. These include Salmonella [35], Mycobacterium tuberculosis [36], Shigella flexneri [37], Streptococcus [38], and L. monocytogenes [39,40]. The cytochrome oxidases have been studied to play a role of in bacterial protection against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%